ChemInform Abstract: An Efficient Synthesis and Applications of Chalcones in Organic Synthesis. Issue 15 (April 2015) - Pareek, Aastha; Rani, Priyanka; Kumar, Navneet; Sharma, Pratima; Kishore, D.
Abstract: Review: 37 refs.